The Study of India's Tax System Analytical: An Analysis of India's Tax System and its Impact on Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2018)
How a nation collects its taxes may have significant effects on its economic growth. The Indiantax system is sophisticated. According to the Indian Constitution's provisions, the three levels ofgovernment share the authority to impose taxes and duties. This study, which relies on secondarysources, analyzed tax revenue from fiscal years 2013–14 through 2017–18, classifying it into direct tax,indirect tax, and its subtypes. The ratio of taxes to GDP is also analyzed.